Presente y futuro de la producción de vacuno de aptitud cárnica en extensivo - Bellido, M. Martín (Archivos de zootecnia, 1995)
Se presenta la producción de carne a nivel mundial, europeo y nacional, haciendo énfasis en los datos de The meat production of the world, Europe and Spain is presented, with enphasis on the Extremadura data. In this region, the number of cattle in 1994 was 462553, of which 319508 were beef cows, managed under extensive conditions. The beef meat produced in extensive system, reached 55199.8 t with a value of 19201.7 millions of pesetas, representing a 20.26 per cent of the total meat produced in the region and the 26.24 per cent of the total value. The steers are feedlot mainly outside the region, due to different causes. The importance of the subsidies coming from the beef cows Commom Market Organization, in the farmers income maintenance, is pointed out. Also, the necessity to improve the breeders association, to comercialize this quality beef, produced under extensive systems compatible with the environment conservation, with the goat to get quality tags for this meat, their promotion and to organice their offer in the market.
Keywords: Dehesa; meat marketing; Quality meat

Presente y futuro de la producción de vacuno de aptitud cárnica en extensivo - Bellido, M Martín (Archivos de zootecnia, 1995)
Se presenta la producción de carne a nivel mundial, europeo y nacional, haciendo énfasis en los datos de The meat production of the world, Europe and Spain is presented, with enphasis on the Extremadura data. In this region, the number of cattle in 1994 was 462553, of which 319508 were beef cows, managed under extensive conditions. The beef meat produced in extensive system, reached 55199.8 t with a value of 19201.7 millions of pesetas, representing a 20.26 per cent of the total meat produced in the region and the 26.24 per cent of the total value. The steers are feedlot mainly outside the region, due to different causes. The importance of the subsidies coming from the beef cows Commom Market Organization, in the farmers income maintenance, is pointed out. Also, the necessity to improve the breeders association, to comercialize this quality beef, produced under extensive systems compatible with the environment conservation, with the goat to get quality tags for this meat, their promotion and to organice their offer in the market.
Keywords: Dehesa; meat marketing; Quality meat